2017
DOI: 10.3389/fphys.2017.00710
|View full text |Cite
|
Sign up to set email alerts
|

Taurine: A Potential Ergogenic Aid for Preventing Muscle Damage and Protein Catabolism and Decreasing Oxidative Stress Produced by Endurance Exercise

Abstract: The aim of this study was to evaluate the effects of taurine and chocolate milk supplementation on oxidative stress and protein metabolism markers, and aerobic parameters in triathletes.Methods: A double-blind, crossover study was conducted with 10 male triathletes, aged 30.9 ± 1.3 year, height 1.79 ± 0.01 m and body weight 77.45 ± 2.4 kg. Three grams of taurine and 400 ml of chocolate milk (TAUchoc), or a placebo (chocolate milk) (CHOC) was ingested post exercise for 8 weeks. Oxidative stress marker levels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 55 publications
1
26
0
3
Order By: Relevance
“…The authors found that the ingestion of taurine improved overall endurance performance in the subjects. This conclusion is consistent with the recent findings that taurine is a potential ergogenic aid for preventing muscle damage, attenuating muscle protein catabolism, decreasing oxidative stress, and improving performance in subjects with endurance exercise (De Carvalho et al 2017;Page et al 2019;Paulucio et al 2017;Waldron et al 2019).…”
Section: Health Benefits Of Taurine Supplementationsupporting
confidence: 92%
“…The authors found that the ingestion of taurine improved overall endurance performance in the subjects. This conclusion is consistent with the recent findings that taurine is a potential ergogenic aid for preventing muscle damage, attenuating muscle protein catabolism, decreasing oxidative stress, and improving performance in subjects with endurance exercise (De Carvalho et al 2017;Page et al 2019;Paulucio et al 2017;Waldron et al 2019).…”
Section: Health Benefits Of Taurine Supplementationsupporting
confidence: 92%
“…The subjects were divided randomly into two groups: the placebo group (n = 7) and the taurine group (n = 7). The taurine group received 3g of taurine per day 7,20 , while the placebo group received 3g of starch flour, which was identical in appearance to taurine capsules.…”
Section: Trial Designmentioning
confidence: 99%
“…The participants were instructed to intake 3 grams of pure taurine 7,20 or placebo, which refers to 3 capsules containing 1g of the supplement, every day in the morning before breakfast, during an eight-week period. The taurine powder was obtained from Ajinomoto (Aminoethylsulfonic Acid, Ajinomoto R, São Paulo, SP) and the capsules were manipulated by the Department of Industrial Pharmacy of the School of Medicine of Ribeirão Preto, University of São Paulo.…”
Section: Supplementation Protocolmentioning
confidence: 99%
See 2 more Smart Citations